Evaluasi Dampak Program Keluarga Harapan (PKH) di Desa Kutukulon Kecamatan Jetis Kabupaten Ponorogo - Aliatun Nisa; Weni Rosdiana; Haryo Kunto Wibisono; Nabila Septia Rosa (Policy and Maritime Review, 2025)
The background of this study is several issues in the implementation of the Family Hope Program, such as inaccurate beneficiary data, dependency on social assistance, and suboptimal empowerment and training efforts to promote economic independence and poverty reduction. The aim of this research is to analyze and describe the impact evaluation of PKH implementation in Kutukulon Village, Jetis District, Ponorogo Regency. This study uses a descriptive qualitative approach based on Samodra Wibawa’s impact evaluation theory, which consists of four indicators: individual, organizational, community, and institutional-social system impacts. Data were collected through interviews, observation, and documentation, and analyzed using data reduction, data display, and conclusion drawing techniques. The findings show that the individual impact is still limited to meeting basic needs and education expenses, and has not significantly improved economic independence, while dependency tendencies remain. At the organizational level, issues include data inaccuracy, limited village authority, and suboptimal mentoring. At the community level, the program has led to perceptions of unfairness, social jealousy, lack of transparency, and confusion in targeting mechanisms. At the institutional level, the data system has not fully reflected the dynamic socio-economic conditions of society. Strengthening assistance, updating data, and developing economic empowerment programs are necessary.